2022
DOI: 10.1038/s41398-022-01914-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous electrical acupoint stimulation for children with attention-deficit/hyperactivity disorder: a randomized clinical trial

Abstract: Little is known about the effects of transcutaneous electrical acupoint stimulation (TEAS) for children with attention-deficit/hyperactivity disorder (ADHD). Here, we carried out a 4 week randomized clinical trial in which patients aged 6–12 years old with an ADHD diagnosis received TEAS or sham TEAS. The primary outcome measure was the investigator-rated Clinical Global Impression-Improvement (CGI-I) score at week 4. Secondary outcomes included changes from baseline to week 4 in the investigator-rated Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…These findings demonstrate that acupuncture can enhance blood oxygen activity in the visual cortex and increase HbO 2 content in areas V1 and V2 ( Chai, 2020 ; Wu, 2022 ). Researchers have used fNIRS to examine brain responses in children with attention-deficit/hyperactivity disorders treated with percutaneous acupoint electrical stimulation ( Zhuo et al, 2022 ). The HbO 2 concentration was measured using a go/no-go task before and after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…These findings demonstrate that acupuncture can enhance blood oxygen activity in the visual cortex and increase HbO 2 content in areas V1 and V2 ( Chai, 2020 ; Wu, 2022 ). Researchers have used fNIRS to examine brain responses in children with attention-deficit/hyperactivity disorders treated with percutaneous acupoint electrical stimulation ( Zhuo et al, 2022 ). The HbO 2 concentration was measured using a go/no-go task before and after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of the recent, included articles revealed that most explored the efficacy and safety of acupuncture as a complementary and alternative therapy for improving general symptoms of patients with NDDs. For example, Zhuo [ 25 ] described acupoint stimulations increased prefrontal cortex blood flow in children with ADHD, with mild adverse events. Hai et al showed therapeutic effects of acupuncture for TD, especially vocal tic, in children [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that mTEAS may improve pregnancy outcomes somewhat, but this finding may be due to the placebo effect of routine procedures; it may also indicate that a weak current or electrodes without electricity are not completely inert ( Zhuo et al, 2022 ). An adequate literature search was conducted for this review, but RCTs were few, and the sample size was insufficient.…”
Section: Discussionmentioning
confidence: 99%